MEDIA LITERACY IN EXTRACURRICULAR ACTIVITIES - Vanek, Katarina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This research has been set in view of the increasing exposure of children and youth to the media and the challenges of the modern education system. The aim was to establish the existence and representation of extracurricular activities in school curricula aimed at media literacy of students in primary schools in the area of Virovitica-Podravina and Požega-Slavonia Counties in the Republic of Croatia. The data were collected by studying the documentation - analysis of 25 school curricula for the 2020/2021 school year, which are available on websites of the schools. The results are described by the descriptive method and point to the existence of extracurricular activities aimed at media literacy of students, but not in all schools. Such extracurricular activities are more represented in higher grades of primary school (5th -8th grade) and are mostly oriented toward journalism, while in lower grades (1st - 4th grade) the most frequent activities are related to Computer Science or a specific aim set within media literacy education. Finally, this research can be a starting point for other research projects for determining the causal links that led to such results and an incentive to improve educational practice in Croatian schools.